2015
DOI: 10.1016/j.jpeds.2015.04.035
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Clinical Trial of Preoperative Feeding to Evaluate Intestinal Barrier Function in Neonates Requiring Cardiac Surgery

Abstract: Objective To evaluate intestinal barrier function in neonates undergoing cardiac surgery using lactulose/mannitol (L/M) ratio measurements and to determine correlations with early breast milk feeding. Study design This was a single-center, prospective, randomized pilot study of 27 term neonates (≥37 weeks gestation) requiring cardiac surgery who were randomized to one of two pre-operative feeding groups: 1) nil per os (NPO) vs. 2) trophic (10 cc/kg/day) breast milk feeds. At three time points (pre-op, post-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 27 publications
1
16
0
1
Order By: Relevance
“…Baseline EAA levels appeared to have a significant correlation with age of patients at surgery, with the highest values in the youngest neonates (r ¼ À.50, P ¼ .006). When baseline features of the six patients who received enteral nutrition before surgery were compared to those who did not, we noticed that they were older (median [IQR], age [days]: 13 [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] No differences in EAA levels at POD2 were noticed between the 12 patients who underwent CPB and 14 patients with off-pump surgery (median difference 0.06, P ¼ .36; Table 2). However, the six patients who required aortic clamping for coarctation repair displayed the lowest EAA levels at POD2, compared to the others (median difference À0.3, P ¼ .04; Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Baseline EAA levels appeared to have a significant correlation with age of patients at surgery, with the highest values in the youngest neonates (r ¼ À.50, P ¼ .006). When baseline features of the six patients who received enteral nutrition before surgery were compared to those who did not, we noticed that they were older (median [IQR], age [days]: 13 [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] No differences in EAA levels at POD2 were noticed between the 12 patients who underwent CPB and 14 patients with off-pump surgery (median difference 0.06, P ¼ .36; Table 2). However, the six patients who required aortic clamping for coarctation repair displayed the lowest EAA levels at POD2, compared to the others (median difference À0.3, P ¼ .04; Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Although no high-level recommendation exists in the cardiac surgery population about when patients can receive enteral nutrition in the postsurgical period, it might be speculated that intestinal function (and eventual translocation) can be affected by intraoperative events, mainly by ischemic pathophysiology. 14 The aim of the present study was to increase our knowledge about EAA perioperative levels, in the specific population of neonates with CHD undergoing cardiac surgery, by exploring variables potentially related to splanchnic perfusion (presence of CPB, shunt-dependent circulation or aortic coarctation, postoperative hemodynamics, and available perfusion indexes) and splanchnic function (postoperative refeeding and feeding intolerance).…”
Section: Introductionmentioning
confidence: 99%
“…19 However, recent publications suggest that preoperative feeds may be safe and may improve postoperative feeding tolerance and other clinical outcomes in this high-risk population. [32][33][34][35] One study found that neonates with hypoplastic left heart syndrome (HLHS) that received preoperative trophic feeds had a shorter duration of postoperative mechanical ventilation, less fluid overload, and earlier postoperative feeding tolerance. 36 The analysis contains all of the expected limitations of a single-center, retrospective cohort study but remains important for showing that preoperative feeds might be safe and positively impact clinical outcomes.…”
Section: Preoperative Feeding In Neonatesmentioning
confidence: 99%
“…Although the study found no difference in rates of feeding intolerance or NEC between the groups, the small sample size was underpowered to detect differences in adverse events. 33 As the field continues to establish the safety and potential advantages of preoperative feeding in ductal-dependent neonates, the more difficult question becomes "when is it not safe to feed?" these tenuous patients.…”
Section: Ductal-dependent Chdmentioning
confidence: 99%
“…S.C. Zyblewski и соавт. [23] предполагают, что при соответствующем мониторировании и стратификации факторов риска доношенные новорожденные со сложными пороками сердца, включающими дуктус-зависимые пороки и наличие единственного желудочка сердца, могут энтерально питаться в предоперационный период. Исследователи считают, что позднее начало энтерального кормления может принести больше вреда, чем пользы, влияя в том числе на нервно-психического развитие новорожденных.…”
unclassified